Peran Guru Fiqih dalam Menanamkan Kebiasaan Shalat Dhuha pada Siswa Madrasah Ibtidaiyah - Lia Yulianti Fajrin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to reveal the efforts of Islamic jurisprudence teachers in getting students used to performing Dhuha prayers at Pamaciran Elementary Madrasah. This habituation is an important part of developing students' religious character through worship practices. The approach used in this study is qualitative with a case study type. The subjects of the study consisted of fifth grade students of Pamaciran Elementary Madrasah, which were determined through snowball sampling techniques. Data were collected through interview methods and observations of worship habituation activities carried out by teachers and students. The results of the study indicate that the efforts of Islamic jurisprudence teachers in getting students used to Dhuha prayers include four main strategies, namely: (1) providing motivation to students, (2) providing direct guidance, (3) training students through routine habits, and (4) conducting regular supervision. The impact of these efforts can be seen from the increasing enthusiasm of students in worship, the ease of students in understanding the procedures for Dhuha prayers, and increasing discipline in carrying out worship. Thus, the role of Islamic jurisprudence teachers is very important in fostering a culture of worship in the madrasah environment.